Perilaku Daya Dukung Gabungan Fondasi Rakit Tiang Pada Tanah Lunak - Yolanda Widyan; Ferry Fatnanta; Syawal Satibi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The development of construction engineering science in water and soft soil areas, to overcome the problem of construction on soft soil, a pile raft foundation solution is chosen. Pile raft foundation system is a blend of pile foundation (pile)with a foundation raft, which works in one unit and simultaneously. Analysis of the bearing capacity of the pile raft foundation is carried out by means of laboratory scale testing and then compared with calculations. In the pile raft foundation, variations in the number of piles were used. The method used to calculate the theoretical bearing data using the Terzaghi method, to obtain the carrying capacity of the test carried out an interpretation of the value of the bearing capacity of the foundation taken from the load value at 25mm settlement, in accordance with ASTM D1143-81. The calculation results and test results show that the combined pile raft foundation can increase the bearing capacity of the foundation. The addition of piles to the raft foundation can reduce settlement and increase the bearing capacity of the foundation. The carrying capacity value is calculated and tested based on a decrease of 25 mm, this is done in order to produce the right results. Keyword: bearing capacity, pile raft, settlement